A case study on risk analysis of machine breakdown using the FMEA method - Fithri Prima; Hasan Alizar; Wisnel; Sultan Fauzi Kesogihan R. (E3S Web of Conferences)
This study addresses the frequent disruptions in PT X, the first cement factory in Indonesia, which affect its productivity and quality. The main problem involves the frequent stoppages of key machinery such as raw mills, kilns, cement mills, and especially coal mills, which are crucial for combustion processes. In 2021, the 6K1 coal mill experienced 384 hours and 38 minutes of downtime, with the Rotary 6K1A03 component being the most problematic, causing 205 out of 359 total disruptions. The Failure Mode and Effect Analysis (FMEA) method was employed to analyze these disturbances. The analysis revealed a critical Risk Priority Number (RPN) value of 5.148, with eight factors exceeding this threshold, including the high current in Rotary 6K1A03, with RPN values of 90, 35, 25, 24, 9, 8, and 6. These critical factors are prioritized for intervention. Consequently, it is imperative to implement management and risk mitigation strategies to address these issues and enhance the operational efficiency of the factory.